Aire controls the recirculation of murine Foxp3+ regulatory T‐cells back to the thymus. Issue 5 (29th January 2018) - Cowan, Jennifer E.; Baik, Song; McCarthy, Nicholas I.; Parnell, Sonia M.; White, Andrea J.; Jenkinson, William E.; Anderson, Graham
Abstract: In the thymus, medullary thymic epithelial cells (mTEC) determine the fate of newly selected CD4 + and CD8 + single positive (SP) thymocytes. For example, mTEC expression of Aire controls intrathymic self‐antigen availability for negative selection. Interestingly, alterations in both Foxp3 + Regulatory T‐cells (T‐Reg) and conventional SP thymocytes in Aire −/− mice suggest additional, yet poorly understood, roles for Aire during intrathymic T‐cell development. To examine this, we analysed thymocytes from Aire −/− mice using Rag2GFP and Foxp3 expression, and a recently described CD69/MHCI subset definition of post‐selection CD4 + conventional thymocytes. We show that while Aire is dispensable for de novo generation of conventional αβT‐cells, it plays a key role in controlling the intrathymic T‐Reg pool. Surprisingly, a decline in intrathymic T‐Reg in Aire −/− mice maps to a reduction in mature recirculating Rag2GFP − T‐Reg that express CCR6 and re‐enter the thymus from the periphery. Furthermore, we show mTEC expression of the CCR6 ligand CCL20 is reduced in Aire −/− mice, and that CCR6 is required for T‐Reg recirculation back to the thymus. Collectively, our study re‐defines requirements for late stage intrathymic αβT‐cell development, and demonstrates that Aire controls a CCR6‐CCL20 axis that determines the developmental makeup of the intrathymic T‐Reg pool. Abstract : In adult mice, recirculating Foxp3 + T‐Reg re‐enter the thymus from peripheral tissues and make a significant contribution to the intrathymic T‐Reg pool. We show that Aire controls this process via a CCL20‐CCR6 axis, and demonstrate a new role for Aire in regulating cell trafficking between the thymus and periphery.